In the Land of the Dammed : Assessing Governance in Resettlement of Ghana’s Bui Dam Project - Asiama, K.O. (2020)
Resettlement resulting from dam construction has raised several concerns due to the negative aftermath impacts. In Ghana, the construction of three hydroelectric dams resulted in large-scale resettlements. Given the little experience that Ghana has in resettlements, it is necessary for a robust monitoring structure for resettlements. However, this was not available in the last resettlement undertaken for the Bui Dam Project. This paper aims at developing an assessment framework for monitoring resettlement activities on customary lands from a good governance perspective. Based on four good governance principles, transparency, public participation and inclusiveness, equity and rule of law and accountability, a good governance assessment framework is built and applied to the Bui Dam Project using a case study approach. Data were collected through interviews and focus group discussion with the key actors of the resettlement project. It was first found that the planning stage of the resettlement came out with a robust plan that was to prevent the impoverishment of the affected persons. However, in the implementation of the resettlement, not all good governance principles were adhered to. In conclusion, it was found that by deconstructing the resettlement process with a good governance framework, the problematic areas of the resettlement can be effectively differentiated between the planning and implementation phases.